Genetic Tracing of Clonal Expansion and Progression of Pancreatic Ductal Adenocarcinoma: A Case Report and Multi-Region Sequencing Analysis - Tachibana, Shion; Mizukami, Yusuke; Ono, Yusuke; Sugiyama, Yuya; Okada, Tetsuhiro; Kitazaki, Arisa; Sasajima, Junpei; Tominaga, Motoya; Sakamoto, Jun; Kimura, Keisuke; Omori, Yuko; Furukawa, Toru; et al. (Frontiers in Oncology, 2020)
Pancreatobiliary tumors frequently contain multiple malignant and precancerous lesions; however, the origin of the driver mutations and the mechanisms that underlie the generation of distinct clones within an organ field remain unclear. Herein, we describe a case of pancreatic ductal adenocarcinomas that primarily involved the distal bile duct and multiple “dispersing” invasive lesions in the pancreatic head. The patient underwent pylorus-preserving pancreaticoduodenectomy with superior mesenteric vein resection, and targeted sequencing of 18 genes associated with pancreatic tumorigenesis and immunohistochemical analysis of RNF43 were performed on each tumor compartment, including the invasive and non-invasive areas. Multi-region sequencing revealed shared KRAS and TGFBR1 mutations in all invasive foci, including those involving the distal bile duct. Distinct KRAS variants were found to be present in other non-continuous and non-invasive lesions in the pancreas. Intraductal lesions with KRAS G12D and RNF43 V50R mutations were evident in the main pancreatic duct. This appeared to be a founder clone, given that the mutation profile was common to the invasive foci as well as the additional high-grade dysplasia harboring ARID1A mutations, thereby suggesting a clonal branch-off during tumor evolution. In addition, we also observed independent intraductal papillary mucinous neoplasms with KRAS G12V and GNAS R201H mutations. This case, together with precise imaging and histological mapping, illustrates the value of genetic tracing for establishing the evolutionary history of heterogeneous tumors in the pancreatobiliary system.